Las causas del auge y la declinación del sistema interamericano de seguridad : una perspectiva latinoamericana. - Muñoz, Heraldo (Estudios Internacionales, 1987)
The Inter-American Security System is in a state of crisis. This diagnosis is widely shared because of the insignificant role that this system played in addressing the serious security problems that have threatened the hemisphere in recent years. However, the current collapse of the Inter-American Security System has a long history; the concept and the security institutions of the hemisphere have been declining in terms of prestige, credibility, and effectiveness for at least the last two decades. This paper aims, rather than attempting a detailed description of its rise and subsequent decline, to identify the main causes of the collapse of the system in order to finally present the vision that many Latin Americans have of what could be the bases for an alternative collective security system.